Utilization of Morphological and Morphometric Data of Amphibians from the Silahisabungan Geosite as Content for the Development of an Amphibian Species Diversity Booklet - Situmorang, Berri; Manurung, Binari (Universitas Islam Negeri Ar-Raniry, 2026)
Amphibian diversity is an important indicator of environmental quality; however, the utilization of local biodiversity data as a learning resource remains limited, resulting in abstract learning processes. This study aimed to analyze the morphological and morphometric variations of amphibians in the Silahisabungan Geosite-Toba Caldera Unesco Global Geopark (TCUGGp) and to utilize these data as contents for developing a biodiversity booklet. A quantitative descriptive method was employed through observation, documentation, and morphometric measurements of 18 species from five families. The parameters measured included snout-vent length (SVL), head length (HL), head width (HW), tibia length (TL), and others. Data were analyzed descriptively and through morphometric comparisons among species and families. The results showed significant variation in body size and proportions, with SVL ranging from 2.48 to 11.78 cm. Differences in morphometric characteristics among families reflect adaptations to their respective habitats. These findings indicate that morphometric data have strong potential as a basis for developing contextual biology. Keywords: Amphibian; Biodiversity; Booklet; Morphometric; Toba Caldera Unesco Global Geopark (TCUGGp).